2002
DOI: 10.1079/bjn2002683
|View full text |Cite
|
Sign up to set email alerts
|

Functional foods and food supplements for athletes: from myths to benefit claims substantiation through the study of selected biomarkers

Abstract: The development of the sports food market and industrial involvement have led to numerous nutritional studies to define the type of nutrients that are most suited to support energy metabolism, fluid balance and muscle function. The key question in many of these studies was: ‘Does the product lead to a significant product/consumer benefit that can be used as a claim on the package?’ New methods and techniques have been developed, partly with sponsorship of the food industry, with the goal of measuring the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The generally higher gastric emptying rate of glucose polymer solutions than that of free glucose solutions [28] may result in increased intestinal absorption and nutrient supply to the active muscles [10]. Solutions containing glucose polymers possess a higher energy density than simple sugar containing beverages with similar osmolality [29] and also show the ability to maximize glycogen re-synthesis in the muscles [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The generally higher gastric emptying rate of glucose polymer solutions than that of free glucose solutions [28] may result in increased intestinal absorption and nutrient supply to the active muscles [10]. Solutions containing glucose polymers possess a higher energy density than simple sugar containing beverages with similar osmolality [29] and also show the ability to maximize glycogen re-synthesis in the muscles [10].…”
Section: Discussionmentioning
confidence: 99%
“…The generally higher gastric emptying rate of glucose polymer solutions than that of free glucose solutions [28] may result in increased intestinal absorption and nutrient supply to the active muscles [10]. Solutions containing glucose polymers possess a higher energy density than simple sugar containing beverages with similar osmolality [29] and also show the ability to maximize glycogen re-synthesis in the muscles [10]. Glucose polymers undergo degradation to glucose by salivary and pancreatic amylases and mucosal glucoamylase in the upper gastrointestinal tract, resulting in a more prolonged absorption, utilization and oxidation than that obtained with simple sugars [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CH21 presented with smaller cottonseed hulls, while there was an increased proportion of the soybean hull pellets. According to Brouns, Van Nieuwenhoven, Jeukendrup, and Lichtenbelt (2002), the isoflavonoids that are present in soybean products may reduce the free radical contents and have antioxidant properties in human health. King, Mano, and Head (1998) observed that lower isoflavonoids values in the milk of cows that were fed silage did not elicit a biological response in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid replacement using isotonic solution may attenuate or prevent many metabolic, cardiovascular, thermoregulatory and performance perturbations [4,5]. Moreover, according to Brouns et al, [6] and Coyle [7], sports drinks without caffeine can help to maintain physiological homeostasis.…”
Section: Introductionmentioning
confidence: 99%